The Issue of Alcohol in Turkey during the 1980s and 1990s - Elife Biçer-Deveci (Revue des Mondes Musulmans et de la Méditerranée)
This article investigates debates about alcohol drinking in Turkey during the 1980s and 1990s. The emphasis is on the global body of knowledge used by the Green Crescent (Yeşilay Cemiyeti), a non-profit organisation that focuses on public health issues in Turkey. This organisation is the most active recipient of scientific facts and concepts provided by the World Health Organisation in Turkey, and it mediates this knowledge for the Turkish-speaking public. It translates reports and produces abridged versions in simpler language to communicate evidence about the harmful effects of drinking, smoking and other addictive substances. However, this translation has taken on a particular meaning in the context of Turkey. It has fostered specific notions about gender roles, nationhood and lifestyles based on conservative ideologies making use of Islamic principles. Yeşilay has played a significant role in connecting scientific knowledge about alcohol with Islamic understandings of morality and in mediating between international anti-alcohol organisations and local religious conservative groups. The study contributes to the understanding that contemporary public health programmes addressing addiction issues are shaped by ideological and religious elements as well as internal social and political dynamics.